Self-care in the context of the person with deficiency - Juliana Balbinot Reis Girondi; Silvia Maria Azevedo dos Santos (Universidade Federal de Santa Maria, 2011)
The dimensions of disability in Brazil is difficult because of limited data and information available nationwide. This is an important issue within public health, although health care to this population falls marginally in the health system. The article aims, from Michel Foucault concept, to consider disabled person's issues and the subjectivity process of self-care ethics and the art of one's existence. Also devotes his reflections on the disability context throughout history until nowadays. It was found necessary to break with the subjectivity concept of, defending a view of self-care, while an instance that nurture the relationship and the development of the disabled person himself and with others. Thus, allowing up new ways of living and thinking about oneself